STUDI TENTANG TOLERANSI BERAGAMA BAGI MAHASISWA-MAHASISWI PERGURUAN TINGGI KOTA KUPANG DALAM TERANG NOSTRA AETATE - Tamelab, Petrus; Bele, Graciana Amanda (Pastoralia Jurnal Penelitian Dosen, 2023)
The Indonesian state hopes that every religious follower will have an attitude of tolerance in social life. This tolerance is alsoexpected to be realized in the campus environment for students. The focus of this research is to study the attitude of tolerance between religious communities in accordance with the teachings of the Catholic Church in the Second Vatican Council document "Nostra Aetate" which explains that the Catholic Church does not reject anything from other religions that is considered true. The method used in this research is descriptive naturalistic. The results of this research show that religious tolerance is allowing and not interrupting other people's religious activities in social interactions or in establishing social relationships. Religious tolerance also means not picking and choosing, not having negative or negative prejudices against other religions, religious fanaticism, considering other religions as infidels, insulting other religious symbols. Kupang city university students have implemented an attitude of tolerance in social interactions. They respect and respect each other's religion and beliefs